Organizational Culture and Leadership Praxis: Basis for a Proposed Leadership Framework - Molo, Addie; Molo, Rexy (Romblon State University Research Journal, 2022)
Organizational culture is broadly considered to be one of the most important factors of organization variables, which also affects the behavior of employees. Cultural diversity in an organization has a significant influence on work behavior, managerial practices, organizational effectiveness, and efficiency. To evaluate the organizational culture and leadership practice, the researchers invited 24 principals, 246 teachers, and 26 stakeholders from the selected elementary schools in San Agustin, Calatrava, and Sta. Maria in the province of Romblon. The collected data were subjected to cool and warm analyses yielding a set of themes and sub-themes that characterized the desired organizational culture and leadership practices. The findings suggest that the organizational culture of the elementary school principals and teachers was vision-, mission-, goal- and objective-oriented. They are motivators who continuously support their members in facing challenges and work demands. In addition, it was also determined that they were good at problem-solving. Finally, this study generated a proposed leadership framework that could potentially help improve the organizational culture and leadership praxis, particularly in the formulation of an instrument or criteria for choosing new school leaders.